Corporate personhood and artists-in-consultancy in recent fiction. Issue 1 (2nd January 2023) - Diamond, Sam
ABSTRACT: This essay considers the figure of the artist-in-consultancy in the recent novel in the context of the concept of 'corporate personhood'. Beginning with a reading of the work of the poet and novelist Ben Lerner, it explores the idea of a frustrated will towards collectivity which might be achieved or understood through the organisational fabric of the corporation and a virtual poetics of failure, a formation which Lerner outlines in his poem 'Dilation'. I track the development of corporate personhood over the twentieth century and define it through a reading of Reinhold Martin's The Organizational Complex before tracing Lerner's idea of a virtual poetics of the corporate in three recent novels: Emily Segal's Mercury Retrograde (2020), Tom McCarthy's Satin Island (2015), and Elvia Wilk's Oval (2019). These works follow protagonists who work on behalf of corporations as consultants, their positions making them archetypal corporate persons. Through narratives of failure and refusal, these novels both embrace and eschew corporate personhood, indulging metafictional tendencies to manifest Lerner's idea of virtual collectivity while further complicating it and suggesting a new configuration of the corporate person and the collective.